Malayāla vivarāṇātmaka granthasūci - University of Kerala. Oriental Research Institute & MSS Library; Śr̲īlēkha, Ke. Ji.; University of Kerala. Oriental Research Institute & MSS Library; University of Kerala. Department of Publications (Tiruvanantapuraṃ : Ōr̲iyant̲al R̲isarcc Inst̲it̲t̲yūṭṭ ānḍ Mānuskr̲ipt̲s Laibrar̲i, 2013)
Descriptive catalog of Malayalam manuscripts in the institute.
In Malayalam.
Keywords: University of Kerala. -- Oriental Research Institute & MSS Library -- Catalogs; University of Kerala. -- Oriental Research Institute & MSS Library; Manuscripts, Malayalam -- India -- Trivandrum -- Catalogs; Manuscripts, Malayalam; India -- Trivandrum; Catalogs